Implementation of Physical Education in Early Childhood Education Institutions - Purnami, Esa Nurwulan; Formen, Ali (BELIA: Early Childhood Education Papers, 2020)
Physical education is one of the areas of education that needs to be taught from an early age because the benefits of physical education are enormous for the physical fitness of children. A healthy child will certainly make the child grow and develop optimally and balance the child's brain well. This study aims to determine how the implementation of physical education at PAUD institutions in the Dukuhwaru Sub-District, Tegal Regency. This research is descriptive quantitative research with a survey research type. The population in this study was 87 teachers and the research sample was 30 teachers from 15 kindergarten institutions in the Dukuhwaru Sub-district, Tegal Regency. The data collection method used was a survey in the form of a questionnaire. The sampling technique was using a purposive sampling technique. The results of this study are in details that show the percentage in several aspects including, aspects of the learning curriculum of 76.67% in the good category, the variety of physical education aspects of 80.00% in various categories, aspects of teachers related to understanding, readiness, and competence of 83,33% in the good category, and the physical and infrastructure facilities aspects of the PAUD institution of 83.33% in the adequate category. If the percentage results from each aspect are calculated, a percentage of 80.00% can be obtained, which means that the implementation of physical education at PAUD institutions in the Dukuhwaru Sub-district, Tegal Regency is included in the category that has been carried out well. The conclusion from this research is that the implementation of physical education learning will be carried out well if all the factors that support the learning are fulfilled, especially in the teaching aspect. Because the teacher aspect is the key to determining success in the implementation of physical education learning.